Ways of Knowing Muslim Cultures and Societies
1 online resource.
Keywords: This volume showcases a variety of innovative approaches to the study of Muslim societies and cultures, inspired by and honouring Gudrun Krämer and her role in transforming the landscape of Islamic Studies. With contributions from scholars from around the world, the articles cover an extraordinarily wide geographical scope across a broad timeline, with transdisciplinary perspectives and a historically informed focus on contemporary phenomena. The wide-ranging subjects covered include among others a “men in headscarves” campaign in Iran, an Islamic call-in radio programme in Mombassa, a refugee-related court case in Germany, the Arab revolutions and aftermath from various theoretical perspectives, Ottoman family photos, Qurʾān translation in South Asia, and words that can’t be read.